THE ROLE OF THE NORTH SUMATERA PROVINCE GENERAL ELECTION SUPERVISORY BODY IN HANDLING 2024 ELECTION VIOLATIONS - Romanus Marbun; Taufiq Siregar; M. Ridha Haykal Akmal (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the role of the General Elections Supervisory Agency (Bawaslu) of North Sumatra Province in handling violations of the 2024 Election. This study uses an empirical juridical method with a statutory regulatory approach and an empirical approach. Data were obtained through interviews and observations, and supported by primary and secondary legal materials. The results show that the Bawaslu of North Sumatra Province has carried out its role in handling election violations in accordance with statutory provisions. However, in practice, there are still normative obstacles in the form of legal gaps and multi-interpretable norms in the Election Law, Bawaslu Regulations, and technical guidelines for handling violations, which affect legal certainty in handling election violations.